2015
DOI: 10.1038/nn.4020
|View full text |Cite
|
Sign up to set email alerts
|

Function and developmental origin of a mesocortical inhibitory circuit

Abstract: Midbrain ventral tegmental neurons project to the prefrontal cortex and modulate cognitive functions. Using viral tracing, optogenetics and electrophysiology, we found that mesocortical neurons in the mouse ventrotegmental area provide fast glutamatergic excitation of GABAergic interneurons in the prefrontal cortex and inhibit prefrontal cortical pyramidal neurons in a robust and reliable manner. These mesocortical neurons were derived from a subset of dopaminergic progenitors, which were dependent on prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 64 publications
5
54
0
Order By: Relevance
“…In the LDTg, Nkx6-1 and Vsx2 label primarily two different cell populations. Recently, glutamatergic tyrosine hydroxylase (TH)-negative neurons have also been demonstrated in the VTA, SNpc/SNpr and RRF (Morales and Root, 2014;Kabanova et al, 2015). We show here that some of them are positive for Nkx6-1 and Vsx2, and their numbers in the SNpr are increased in the Tal1 cko and Gata2 cko ; Gata3 cko mutants.…”
Section: Development Of the Excitatory Neurons Regulating The Monoamisupporting
confidence: 48%
See 1 more Smart Citation
“…In the LDTg, Nkx6-1 and Vsx2 label primarily two different cell populations. Recently, glutamatergic tyrosine hydroxylase (TH)-negative neurons have also been demonstrated in the VTA, SNpc/SNpr and RRF (Morales and Root, 2014;Kabanova et al, 2015). We show here that some of them are positive for Nkx6-1 and Vsx2, and their numbers in the SNpr are increased in the Tal1 cko and Gata2 cko ; Gata3 cko mutants.…”
Section: Development Of the Excitatory Neurons Regulating The Monoamisupporting
confidence: 48%
“…GABAergic SNpr is the main output source of the basal ganglia and projects to brain regions important for activation of voluntary movements. Furthermore, some VTA GABAergic and glutamatergic neurons project to the forebrain and regulate pathways involved in associative learning (Fields et al, 2007;Brown et al, 2012;Kabanova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot exclude the contribution of D2R-expressing pyramidal neurons that may also have elevated levels of βarr2 and GRK2. However, DA released by PFC-projecting mesocortical DA neurons inhibits pyramidal neurons primarily by activating interneurons (82), suggesting a temporally preceding role for FSIs. To target the exact subtype of cortical neurons for more specific behavioral analyses would require developing novel Cre driver lines involving at least tripleintersectional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, new studies searching for the co-release of glutamate by dopaminergic axons in the PFC have shown two opposite results. One study showed that dopaminergic axons do not co-release glutamate in the PFC (Mingote et al, 2015), whereas other works strongly suggested not only co-release of glutamate in PFC (Kabanova et al, 2015; Ellwood et al, 2017), but that these axons specifically innervate GABAergic fast-spiking interneurons (Kabanova et al, 2015) suggesting a specific control of the activity in PFC through the VTA→PFC(interneurons)→PFC(projection-neurons) circuit. However, the wide distribution of the dopaminergic cells from the VTA projecting to the PFC (Morales and Root, 2014) suggested an heterogeneous innervation onto the different PFC cell types.…”
Section: Introductionmentioning
confidence: 99%
“…This last finding provided evidence that not all post-synaptic targets of the dopaminergic neurons receive the co-release of dopamine-glutamate. Consequently, current research has focused on investigating whether dopaminergic axons co-release glutamate at their different targets (Kabanova et al, 2015; Ellwood et al, 2017; Mingote et al, 2017). Specific to our research, the first studies documenting the possibility that the VTA axons may release glutamate on prefrontal cortex (PFC) neurons were done by extracellular electrical stimulation in the VTA while recording PFC neurons (Mercuri et al, 1985; Lavin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%